Adjuvant Transarterial chemoembolization does not influence recurrence-free or overall survival in patients with combined hepatocellular carcinoma and Cholangiocarcinoma after curative resection: a propensity score matching analysis - Liu, Wei-Ren; Tian, Meng-Xin; Tao, Chen-Yang; Tang, Zheng; Zhou, Yu-Fu; Song, Shu-Shu; Jiang, Xi-Fei; Wang, Han; Zhou, Pei-Yun; Qu, Wei-Feng; Fang, Yuan; Ding, Zhen-Bin; et al. (BMC cancer, 2020)
The prognosis of patients with combined hepatocellular carcinoma and intrahepatic cholangiocarcinoma (CHC) is usually poor, and effective adjuvant therapy is missing making it important to investigate whether these patients may benefit from adjuvant transarterial chemoembolization (TACE). We aimed to evaluate the efficiency of adjuvant TACE for long-term recurrence and survival after curative resection before and after propensity score matching (PSM) analysis. In this retrospective study, of 230 patients who underwent resection for CHC between January 1994 and December 2014, 46 (18.0%) patients received adjuvant TACE. Univariate and multivariate regression analyses were used to identify the independent predictive factors of survival. Cox regression analyses and log-rank tests were used to compare overall survival (OS) and disease-free survival (DFS) between patients who did or did not receive adjuvant TACE. A total of 230 patients (mean age 52.2 ± 11.9 years; 172 men) were enrolled, and 46 (mean age 52.7 ± 11.1 years; 38 men) patients received TACE. Before PSM, in multivariate regression analysis, γ-glutamyl transpeptidase (γ-GT), tumour nodularity, macrovascular invasion (MVI), lymphoid metastasis, and extrahepatic metastasis were associated with OS. Alanine aminotransferase (ALT), MVI, lymphoid metastasis, and preventive TACE (HR: 2.763, 95% CI: 1.769-4.314, p < 0.001) were independent prognostic factors for DFS. PSM created 46 pairs of patients. Before PSM, adjuvant preventive TACE was not associated with an increased risk of OS (HR: 0.911, 95% CI: 0.545-1.520, p = 0.720) or DFS (HR: 3.345, 95% CI: 1.686-6.638, p = 0.001). After PSM, the 5-year OS and DFS rates were comparable in the TACE group and the non-TACE group (OS: 22.7% vs 14.9%, respectively, p = 0.75; DFS: 11.2% vs 14.4%, respectively, p = 0.06). The present study identified that adjuvant preventive TACE did not influence DFS or OS after curative resection of CHC.